COMMUNICATIONS, HEALING AND POWER (Revista Internacional de Folkcomunicação, 2024)
The missionaries of the Society of Jesus emerged as significant social and political agents in the Colony, allowing the presence of the crown to be felt. As these men took on the responsibility for the health care of the colony's inhabitants, this enabled the Order to build a significant body of knowledge, the restricted circulation of which among its members conferred political importance upon them in the Portuguese Court. Communication, in this context, is positioned as a tool for gathering power in the face of situations experienced by the missionaries, due to its political dimension. Lastly, we seek to highlight the role of the circulation of missionary knowledge in the process of power configuration in the colonial world.